Trickbox of Memory Essays on Power and Disorderly Pasts - Macgilchrist, Felicitas; Metro, Rosalie (punctum books, 2020)
"Reach into this trickbox of memory and rummage around: you may find a tiny spaceship, or perhaps a signpost, a parade, a raised fist, an entire museum. The essays in Trickbox of Memory: Essays on Power and Disorderly Pasts draw on literary criticism, post-qualitative inquiry, new materialism, and political activism to dismember and reanimate the field of memory studies. In the trickbox, concepts rub up against each other, pieces chip off, things leak, glitter gets everywhere. Things are damaged, their edges are ragged. Some show the potential for repair in the future. The chapters in this volume respond to the observation that in today's moment of political danger, "expected" pasts can easily be instrumentalized in the service of fascism. Trickbox of Memory interrupts the "expected" to throw history into disarray by focusing on the subtlety of how power relations are enacted and contested in reference to the past, assembling a transnational constellation of scholars and practitioners who offer new tricks for working critically with disorderly pasts."